The magnitude and impact of the Youngest Toba Tuff super-eruption - Costa, Antonio; Smith, Victoria C.; Macedonio, Giovanni; Matthews, Naomi E. (Frontiers in Earth Science, 2014)
Super-eruptions, orders of magnitude larger than eruptions experienced in historic times, have devastated wide areas by pyroclastic flows, covered continent-size areas by ash fallout, and injected large quantities of aerosols into the stratosphere affecting global climate. The Youngest Toba Tuff (YTT) is the largest known super-eruption in the Quaternary. Here we reconstructed the ultra-distal volcanic ash dispersal during this super-eruption using a computational ash dispersal model, which provides insights into the eruption dynamics and the impact of the event. The method uses a 3D time-dependent tephra dispersion model, a set of wind fields, and several tens of thickness measurements of the YTT tephra deposit. Results reveal that the YTT eruption dispersed ~8600 km3 (~3800 km3 dense rock equivalent, DRE) of ash, covering ~40 million km2 with more than 5 mm of ash. These new fallout volume estimations indicate that the total volume of the material erupted (including the massive pyroclastic density current, 1500 km3 DRE, deposits on Sumatra) was ~5300 km3 DRE. Simulation results indicate that the eruption had a very large mass flow rate and that the umbrella cloud, associated with the eruption plume, spread as an enormous gravity current around the neutral buoyancy level. The YTT tephra forms a key chronostratigraphic marker in the sedimentary sequences, and is particularly useful for constraining the age of the palaeoenvironmental and archaeological records, and synchronizing these archives to investigate temporal relationships. These new constraints on the extent of the YTT deposit are therefore particularly useful for cryptotephra studies that aim to find non-visible tephra layers for these chronological purposes. This method used to constrain volcanological parameters of eruptions in the past provides insights into the dispersal processes, and allows the amount of volatiles released to be estimated which is crucial to assessing the impact of such events.